The Chinese translation of Russian literature : three studies - Gamsa, Mark, 1970- (Sinica Leidensia, 2008)
Offers a history of the translation, transmission and interpretation of modernist Russian literature in China during the first half of the 20th century. This book shows the crucial role of English, German and Japanese translations in mediating knowledge of Russian literature in China.